Comparative Effectiveness of Carotid Artery Stenting Versus Carotid Endarterectomy Among Medicare Beneficiaries. (May 2016) - Jalbert, Jessica J.; Nguyen, Louis L.; Gerhard-Herman, Marie D.; Kumamaru, Hiraku; Chen, Chih-Ying; Williams, Lauren A.; Liu, Jun; Rothman, Andrew T.; Jaff, Michael R.; Seeger, John D.; Benenati, James F.; Schneider, Peter A.; et al.
Abstract : Background—: Effectiveness of carotid artery stenting (CAS) relative to carotid endarterectomy (CEA) among Medicare patients has not been established. We compared effectiveness of CAS versus CEA among Medicare beneficiaries. Methods and Results—: We linked Medicare data (2000–2009) to the Society for Vascular Surgery's Vascular Registry (2005–2008) and the National Cardiovascular Data Registry's (NCDR) Carotid Artery Revascularization and Endarterectomy Registry (2006–2008/2009). Medicare patients were followed up from procedure date until death, stroke/transient ischemic attack, periprocedural myocardial infarction, or a composite end point for these outcomes. We derived high-dimensional propensity scores using registry and Medicare data to control for patient factors and adjusted for provider factors in a Cox regression model comparing CAS with CEA. Among 5254 Society for Vascular Surgery's Vascular Registry (1999 CAS; 3255 CEA) and 4055 Carotid Artery Revascularization and Endarterectomy Registry (2824 CAS; 1231 CEA) Medicare patients, CAS patients had a higher comorbidity burden and were more likely to be at high surgical risk (Society for Vascular Surgery's Vascular Registry: 96.7% versus 44.5%; Carotid Artery Revascularization and Endarterectomy Registry: 71.3% versus 44.7%). Unadjusted outcome risks were higher for CAS. Mortality risks remained elevated for CAS after adjusting for patient-level factors (hazard ratio, 1.24; 95% confidence interval, 1.06–1.46). After further adjustment for provider factors, differences between CAS and CEA were attenuated or no longer present (hazard ratio for mortality, 1.13; 95% confidence interval, 0.94–1.37). Performance was comparable across subgroups defined by sex and degree of carotid stenosis, but there was a nonsignificant trend suggesting a higher risk of adverse outcomes in older (>80) and symptomatic patients undergoing CAS. Conclusions—: Outcomes after CAS and CEA among Medicare beneficiaries were comparable after adjusting for both patient- and provider-level factors. Abstract : Supplemental Digital Content is available in the text.